1972
DOI: 10.1042/bj1291071
|View full text |Cite
|
Sign up to set email alerts
|

Species variations in the threshold molecular-weight factor for the biliary excretion of organic anions

Abstract: 1. The excretion in the bile and urine after intravenous injection of 16 organic anions having molecular weights between 355 and 752 was studied in female rats, guinea pigs and rabbits. 2. These compounds were mostly excreted unchanged, except for three of them, which were metabolized to a slight extent (<7% of dose). 3. The rat excreted all the compounds extensively (22–90% of dose) in the bile. 4. In guinea pigs four of the compounds with mol.wt. 355–403 were excreted in the bile to the extent of 7–16% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
71
1
1

Year Published

1973
1973
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(78 citation statements)
references
References 18 publications
5
71
1
1
Order By: Relevance
“…The radiation dose was set at about 3.70 MBq/kg. For the pharmacokinetic studies, blood was collected from the caudal vein (rats), an auricular vein (rabbits), a femoral vein (monkeys), or the abdominal aorta (at 120 hr only for rats and rabbits) 1, 2, 4, 6 (rats only), 8,10,12,24,48,72, and 120 hr after administration. For the excretion studies, after administration, animals were housed individually in metabolic cages to allow separate collection of urine and feces.…”
Section: Animal Husbandrymentioning
confidence: 99%
“…The radiation dose was set at about 3.70 MBq/kg. For the pharmacokinetic studies, blood was collected from the caudal vein (rats), an auricular vein (rabbits), a femoral vein (monkeys), or the abdominal aorta (at 120 hr only for rats and rabbits) 1, 2, 4, 6 (rats only), 8,10,12,24,48,72, and 120 hr after administration. For the excretion studies, after administration, animals were housed individually in metabolic cages to allow separate collection of urine and feces.…”
Section: Animal Husbandrymentioning
confidence: 99%
“…4. These results together with data from the literature suggest that the molecular weight at which the excretion of dications in the bile exceeds 10% of the dose is in the region of 500-600, which differs from the values for monocations (Hughes et al, 1973) and anions (Millburn et al, 1967;Hirom et al, 1972).…”
mentioning
confidence: 45%
“…4. These results together with data from the literature suggest that the molecular weight at which the excretion of dications in the bile exceeds 10% of the dose is in the region of 500-600, which differs from the values for monocations (Hughes et al, 1973) and anions (Millburn et al, 1967;Hirom et al, 1972).From a study of the biliary excretion in the rat, guinea pig and rabbit of some monoquaternary ammonium or pyridinium cations, Hughes et al (1973) suggested that there is a molecular-weight threshold of about 200±50 for the significant (i.e. 10% or more of the dose) biliary excretion of monoquaternary nitrogen cations in these species.…”
mentioning
confidence: 48%
See 1 more Smart Citation
“…Rats (three male and three female) with bile-duct and ureter cannulae received intravenous injections of potassium diethylstilboestrol mono [35S] At relatively high dosages there was no significant biliary elimination of either mono-or di-sulphate esters of diethylstilboestrol, although diethylstilboestrol disulphate does fulfil the requirements of molecular weight, anionic character and lipophilic nature suggested (Hirom et al, 1972) as necessary for biliary elimination. Either there is no mechanism for the biliary elimination of these esters or the metabolism is so rapid that no biliary elimination of the compound is observed.…”
Section: Experiments With Diethylstilboestrolmono[35s]sulphatementioning
confidence: 99%